Trophic strategies of two newt populations living in contrasting habitats on a Mediterranean island. Issue 1 (2nd January 2020) - Rosa, Giacomo; Costa, Andrea; Salvidio, Sebastiano
Abstract : In amphibians, the study of trophic niche is important to better understand the species ecological adaptation, in particular along gradients or in heterogeneous habitats. In this framework, we analysed the trophic strategies of two populations of the endemic Corsican brook newt Euproctus montanus, one living in a Mediterranean lowland and the other in a mountain stream. In both sites, we performed dietary analysis using stomach flushing and assessed the available invertebrate prey community. Further, we estimated newt density using removal sampling. Streams were similar in invertebrate prey abundance ( P = 0.15), but differed in prey diversity ( P < 0.001), the Mediterranean lowland site possessing a higher diversity of invertebrate prey. The newts' trophic strategies were analysed at the population level and also at the individual one to assess in detail the trophic specialization. In both sites newt density was similar and the population realized trophic niche displayed a large overlap with the available prey community. Therefore, both populations behaved as broad trophic generalists. However, in the Mediterranean lowland stream, where available resources were more diverse, there was evidence of a significant degree of individual trophic specialization. This finding is consistent with the classic niche variation hypothesis, that predicts a higher individual differentiation in presence of high resource diversity.